Impact of economic crises on mortality: The case of Mexico - Arceo Gómez, Eva Olimpia (Estudios Económicos de El Colegio de México, 2010)
We analyze the impact of economic crises on mortality in Mexico. Identification of that effect is difficult because de GDP itself may be a function of health. In order to solve for endogeneity, we propose the use of two sets of instrumental variables at the state level. Our findings suggest that one percent decrease in GDP would lead to an increase of 0.5 percent of the mortality rates. Children and the elderly constitute the most vulnerable groups. The findings imply that the 2008 crisis sent us back to 2001 infant mortality levels, reversing Mexico’s progress to attain that MDG.